Di‐genic inheritance of germline POLE and PMS2 pathogenic variants causes a unique condition associated with pediatric cancer predisposition. Issue 4 (7th January 2022) - Michaeli, Orli; Ladany, Hagay; Erez, Ayelet; Ben Shachar, Shay; Izraeli, Shai; Lidzbarsky, Gabriel; Basel‐Salmon, Lina; Biskup, Saskia; Maruvka, Yosef E.; Toledano, Helen; Goldberg, Yael
Abstract: Polymerase proofreading‐associated polyposis (PPAP) and Lynch syndrome, caused by mutated POLE and mismatch repair (MMR) genes, respectively, are associated with adult‐onset cancer. PPAP and MMR‐deficient tumors are both hypermutated, and each has a unique mutational signature. We describe a 4.5‐year‐old boy with multiple café au lait spots who presented with metastatic Sonic Hedgehog‐activated medulloblastoma, with partial response to intensive chemotherapy and immunotherapy. The tumor showed microsatellite stability, loss of PMS2 nuclear expression, and an exceptionally high tumor mutational burden of 276 Mut/Mb. Germline molecular analysis revealed an inherited heterozygous pathogenic POLE variant and a de novo heterozygous PMS2 pathogenic variant. The tumor featured the MMR, POLE, and POLE+MMR mutational signatures. This is the first description of a di‐genic condition, which we named "POL‐LYNCH syndrome, " manifested by an aggressive ultra‐mutant pediatric medulloblastoma with a unique genomic signature. Abstract : We describe a 4.5‐year‐old boy with multiple café au lait spots and metastatic medulloblastoma, which showed microsatellite stability and an exceptionally high tumor mutational burden. Germline molecular analysis revealed an inherited heterozygous pathogenic POLE variant and a de novo heterozygous PMS2 pathogenic variant.